Malassezia spp. Yeasts of Emerging Concern in Fungemia - Rhimi, Wafa; Theelen, Bart; Boekhout, Teun; Otranto, Domenico; Cafarchia, Claudia (Frontiers in Cellular and Infection Microbiology, 2020)
Malassezia spp. are lipid-dependent yeasts, inhabiting the skin and mucosa of humans and animals. They are involved in a variety of skin disorders in humans and animals and may cause bloodstream infections in severely immunocompromised patients. Despite a tremendous increase in scientific knowledge of these yeasts during the last two decades, the epidemiology of Malassezia spp. related to fungemia remains largely underestimated most likely due to the difficulty in the isolation of these yeasts species due to their lipid-dependence. This review summarizes and discusses the most recent literature on Malassezia spp. infection and fungemia, its occurrence, pathogenicity mechanisms, diagnostic methods, in vitro susceptibility testing and therapeutic approaches.